PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS IV PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Sharfinabilla, Kalia Zalfa; Deviyanti Pangestu; Siti Nuraini; Ari Sofia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The primary issue addressed in this study is the low creative thinking skills of students in the Pancasila Education subject at SD IT Pelita Khoirul Ummah. This study aims to determine the effect of Canva-based interactive learning media on the creative thinking skills of fourth-grade students in Pancasila Education learning. This research employs a quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design. The population consisted of 54 students, with a sample comprising 27 students from class IVA and 27 students from class IVB, selected using a saturated sampling technique. Data collection techniques included tests (pre-test and post-test) as well as non-test methods (observation and documentation). The data were analyzed using N-Gain and t-tests. The results indicate that the use of interactive learning media, specifically Canva, has a significant impact on the creative thinking skills of fourth-grade students in Pancasila Education. This is evidenced by an N-Gain score of 0.51, which falls into the medium category. Furthermore, the t-test results yielded a significance value of < 0.001, indicating a significant difference between the use of Canva media compared to standard reading books and student worksheets (LKPD).